A qualitative investigation of the influence of time since graduation on English dentists’ approach to the care of young children - YVONNE-MARIE, KEITH MARTIN, LAURA, ANTHONY STEPHENSON, ANTHONY GEORGE, & MARTIN TICKLE (IAPD and Blackwell, 2007)
Understanding how the dental care of young children is approached and delivered is important, as the care provided can have longlasting consequences on the dental health of individuals and their attitudes to accessing dental care. In England, approximately 40% of 5-year-old children have dental caries and this statistic has remained largely unchanged over the last 20 years.